Analisis kritis kasus etika bisnis: Menggabungkan rasionalitas dan hati nurani - Triyana, Angelia (Maliki Interdisciplinary Journal, 2024)
This article, titled "Critical Analysis of Business Ethics Cases: Combining Rationality and Conscience," explores the essential integration of rational decision-making and moral conscience in the realm of business ethics. It emphasizes that while rationality often drives systematic and profit-oriented decision-making, it must be balanced with an understanding of conscience, which serves as a moral guide in complex ethical situations. The discussion highlights the significance of conscience in fostering sustainability practices, as evidenced by Gajanayake et al., who assert that ethical motivations are fundamental to managerial decision-making. Furthermore, the dynamic nature of conscience encourages reflective practices that uphold moral integrity, particularly in challenging environments. The limitations of the rational choice model are critiqued, suggesting that a more holistic approach that incorporates both rationality and conscience is necessary for a comprehensive understanding of ethical behavior in business. Additionally, the article underscores the practical implications of integrating ethical considerations into organizational culture, emphasizing the importance of supporting individuals in making conscientious decisions. Ultimately, this critical analysis reveals the intricate interplay between rationality and conscience, advocating for a more responsible and sustainable approach to business ethics.